(untitled) - Sander, Peter J. ([Irvine, Calif.], 2007)
This guide goes where no personal finance book has gone before—to examine personal finances from the point of view of the entrepreneur. An entrepreneur’s business and personal finances are joined at the hip. Financial success or failure in the business drives personal finances; likewise, success or failure with individual finances will ultimately drive business outcomes. This guide drills down into the connective tissue between the two and shows you how to apply your management do-it-yourself skills to your personal finances. It covers organization structure, taxes, budgeting, cash flow, debt, risk management, investing, retirement planning, and the eventual transition of the business—all places where your individual and business finances meet, again and again.
Keywords: Businesspeople,Doanh nhân; Finance, Personal.,Tài chính, cá nhân